Asymptomatic intramural esophageal dissection: a case report and literature review - Cheng, Gong; Wang, Li; You, Jiateng; Cheng, Liangliang; Yang, Fan; Wang, Xiaolu; He, Fang; Li, Changjin; Wei, Xiaoguo (Medicine, 2025)
Rationale: - Intramural esophageal dissection (IED) is a rare condition, with asymptomatic cases not previously reported. This report aims to highlight an incidental finding of IED in a patient undergoing routine gastroscopy. - Patient concerns: - A 41-year-old male with decompensated liver cirrhosis underwent gastroscopy, revealing IED without prior symptoms or history of esophageal surgery or injury. - Diagnoses: - IED. - Interventions: - Conservative treatment was chosen due to the patient’s poor coagulation function and low platelet count, avoiding potential complications such as swallowing difficulties or hematemesis. - Outcomes: - The patient remained asymptomatic and stable during follow-up. - Lessons: - This case underscores the importance of considering IED in differential diagnoses, even in asymptomatic patients, and highlights conservative management’s efficacy in specific scenarios.